Product Design of Portable Nail Puller for Practical Work - Kamarulzaman, Muhammad Amirul Ashraf; Rozali, Mohd Zulfadli; Yunus, Faizal Amin Nur (Research and Innovation in Technical and Vocational Education and Training, 2021)
Failure to pull the nail properly without damaging the material is a major problem for the user. In this regard, this study was developed to develop a portable nail pull tool that can be used to remove nails without wasting material. This study was conducted to develop a portable nail pull tool for practical training to replace existing tools manually. Through this manual action, users encounter problems when removing nails without damaging the workpiece and materials used. This product was developed using the ADDIE model as a development model. There are five phases in the ADDIE model namely the analysis, design, development, design implementation and evaluation phases. The development of this simulation uses Solidwork's designing application to develop it. Three experts have been selected to evaluate the design and functionality of the Portable Nail Puller Simulation using questionnaires and expert endorsements. Data analysis is done using percentage method. All experts agree on the development of this Nail Puller Simulation where the functionality level is 100%. Therefore, the development of these simulations can provide a clear and detailed picture to the user to develop the actual tool.